Conflict and the separateness of peoples: investigating the relationship between multiplicity, inequality and war. Issue 3 (2nd April 2020) - Lees, Nicholas
ABSTRACT: The discipline-defining claim that anarchy leads inevitably to security-competition and war between states is unsustainable. This article investigates whether the concept of multiplicity can offer a reintegrated account of insecurity in world politics. As highlighted by rational choice approaches, substantive conflicts of interest are a necessary condition for organized violence to be a permanent possibility within, across and between societies. A materialist argument is presented that the most enduring incompatible interests arise from clashes over the rules of economic appropriation and redistribution, and the appropriate boundaries between social groups. Historically, unevenness and the possibility for exploitation have created structural pressures towards simultaneous social stratification and the institutionalization of inter-societal warfare. Because of the central importance of social boundaries for structural inequalities, multiplicity has profound implications for both patterns of organized violence and the fundamental issue in the study of politics: who gets what, when and how.